Pembuatan Spot Foto PIJEN HILLS Upaya Pengembangan Potensi Pariwisata yang ada Di Desa Kayukebek Kecamatan Tutur Kabupaten Pasuruan - Saqoty, Rosi Assariyu; Amalia, Nadhifah Hikma Adi; Setyawan, Achmad Indra; Firmansyah, Yoga Ardianto; Abdillah, Okky Zubairi (Wadah Inovasi Indonesia, 2024)
The tourist attractions located in Kayukebek Village, Tutur District, Pasuruan Regency are minimal, but have extraordinary potential to be developed. With stunning views and a comfortable atmosphere, this village has the opportunity to become a leading tourist destination. To increase its attractiveness, a viewing point was built on the road to Surorowo Hamlet. This photo spot offers a unique experience for visitors, allowing them to enjoy the beauty of nature while sharing the moment on social media. It is hoped that this development can attract more tourists and increase awareness of the village's potential. Apart from that, more intensive promotional efforts will help introduce the beauty of Kayukebek to the wider public.